anonymous
  • anonymous
I have a question from the book "Calculus" by Gilbert Strang. It's available for download here. Anyway on p7 is the question: Find the linear function with f(t+2)=f(t)+6 and f(1)=10. The answer is 3t+7. I cannot even begin to figure out a way to find this out. please help, thanks!
OCW Scholar - Single Variable Calculus
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Never mind, I figured it out... had to go through an old math book. If anyone is wondering: First you need to solve for the slope by substituting the known value of f(1): f(t)=vt+C (the goofy notation for slope-intercept used in this section of the book) v(1+2)+c=(1+c)+6 3v+c=v+c+6 -c -c 3v=v+6 -v -v 2v=6 v=3 then put or newly obtained v value into f(1)=10 f(t)=vt+c 3(1)+c=10 3+c=10 c=7 3t+7 So frustrating, I'm getting for calculus this fall and I'm struggling from the start!
anonymous
  • anonymous
Hi!! I think you can solve the problem also by this way. You Know that f(1) = 10 So f(1 +2) = f(1) +6 I have only replaced t=1 f(3)= 16 Now you have two point A(1;10) and B(3;16) , and you can use this formula to find the equation of the linear function \[(y -ya) /( yb -ya) = (x - xa) / (xb - xa)\] Byee:)
anonymous
  • anonymous
Thank you that is actually a lot easier!

Looking for something else?

Not the answer you are looking for? Search for more explanations.